Térmitas em fragmentos de floresta atlântica: estrutura das taxocenoses, variabilidade genética e efeitos da matriz de cana-de-açúcar sobre o isolamento de populações - Couto, Alane Ayana Vieira de Oliveira (2018)
Termites (Blattodea: Isoptera) are abundant in tropical forests and important elements within the ecological processes of dynamics related to energy flow and nutrient cycling. The Atlantic Forest is one of the largest tropical forests of the world and hold around 1% to 8% of the biodiversity of the world. Despite that, it has suffered extensively by environmental fragmentation, which is largely due to the expansion of agricultural frontiers. The present study aims to analyze the effect of habitat fragmentation on the structure of termites assemblages and genetic diversity of populations and the influence of the sugarcane matrix on the isolation of populations in Atlantic Forest remnants in the Northeast of Brazil. This thesis is divided into 4 chapters. Namely: (1) General introduction; (2) Sharing of termites (Blattodea: Isoptera) between sugarcane matrices and Atlantic Forest fragments in Northeast Brazil that aimed to compare termite assemblages of fragments of the Atlantic Forest with that of the sugarcane matrices that surround them. Species richness, relative abundance and composition differed significantly between forests and the matrices, with the presence of unique species in each environment. The majority of the species found in the matrices do not cause damage to the crop, but instead act in the processes of soil decomposition and formation, thereby contributing to increased productivity; (3) Termites in Atlantic Forest remnants surrounded by sugarcane plantations: influence of attributes of the landscape, remnants and vegetation on the structure of assemblages, whose aimed is to investigate the influence of the attributes of landscape, fragments and vegetation on the structure of termite assemblages in Atlantic Forest fragments surrounded by sugarcane matrix in Northeast Brazil. The assemblages’ functional structure was similar between the fragments. Neither the richness nor the number of termite encounters were explained by the landscape variables, the fragments nor the vegetation, but the species composition was positively correlated with the fragment shape. It is concluded that is possible to create a scenario where forest remnants remain functionally connected and able to sustain a high diversity while maintaining ecosystem services and functions; (4) Effect of environmental fragmentation on Embiratermes neotenicus (Termitidae: Syntermitinae) in an Atlantic Forest landscape in Northeast Brazil, whose aim was to investigate whether the fragmentation of the Atlantic Forest by sugar cane cultivation has affected the genetic diversity of populations of E. neotenicus in 14 forest fragments. There was no relation between genetic variability and fragment characteristics. There was low genetic structuration at the population level, which can be explained by the great longevity of the colonies, which allows for several events of dispersion and colonization of fragments, which is facilitated by the seasonality of the sugarcane matrix.